Pengaruh Kompensasi, Motivasi Kerja, Dan Lingkungan Kerja Terhadap Loyalitas Kerja Generasi Milenial Di Kota Administrasi Jakarta Barat - Ilham Kurnia, (2021)
This study aims to determine the effect of compensation on the work loyalty of the millennial generation in the city of West Jakarta Administration, the work motivation of the millennial generation in the administrative city of West Jakarta and the work loyalty of the millennial generation in the administrative city of West Jakarta, as well as the work environment on the work loyalty of the millennial generation in the city of West Jakarta. West Jakarta administration. The population selected in this study is the millennial generation who work and live in the administrative city of West Jakarta. The selected sample collection technique is non-probability sampling with the type of purposive sampling. The source of data in this study was obtained from distributing questionnaires to 100 respondents. The analytical tool used to assist this research is SmartPLS 3.0. Furthermore, the results given in this study are (1) compensation has a significant effect on work loyalty. (2) work motivation has no significant effect on work loyalty. (3) the work environment has no significant effect on work loyalty. Keywords: Compensation, Work Motivation, Work Environment and Work Loyalty.